2017
DOI: 10.1093/ejcts/ezx263
|View full text |Cite
|
Sign up to set email alerts
|

Novel perspective to evaluate the safety of segmentectomy: clinical significance of lobar and segmental lymph node metastasis in cT1N0M0 lung adenocarcinoma†

Abstract: Dissection of intrapulmonary LSNs reduces the false-negative rate of lymph node metastasis. Solid nodule, non-lepidic predominant invasive adenocarcinoma, lung adenocarcinoma larger than 2 cm in maximum diameter or with elevated serum carcinoembryonic antigen level (>5 ng/ml) might not be suitable for segmentectomy. The lymph node sampling area during segmentectomy should include adjacent LSNs of the target segment. When metastasis to the adjacent LSNs is confirmed by fast-frozen pathology, segmentectomy would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Although currently lobectomy with hilar and mediastinal lymph node dissection was still the standard treatment for early-stage lung cancers, for the peripheral small lung adenocarcinomas ≤2 cm, limited resection such as wedge resection or segmentectomy may be comparable to the lobectomy in the outcome, in such case, STAS remains to be a recurrence or metastasis risk factor. Therefore, distinguishing of STAS on frozen diagnostic sections would be beneficial for surgical strategy whether partial lung resection is enough or not (19,20). In our experience, the dilemma of frozen diagnosis for STAS is to distinguish it from macrophages.…”
Section: Discussionmentioning
confidence: 96%
“…Although currently lobectomy with hilar and mediastinal lymph node dissection was still the standard treatment for early-stage lung cancers, for the peripheral small lung adenocarcinomas ≤2 cm, limited resection such as wedge resection or segmentectomy may be comparable to the lobectomy in the outcome, in such case, STAS remains to be a recurrence or metastasis risk factor. Therefore, distinguishing of STAS on frozen diagnostic sections would be beneficial for surgical strategy whether partial lung resection is enough or not (19,20). In our experience, the dilemma of frozen diagnosis for STAS is to distinguish it from macrophages.…”
Section: Discussionmentioning
confidence: 96%
“…Xiao et al conducted a prospective study and the results showed that it was possible for lung cancer to metastasize to the unaffected segment within the same lobe. 16 Therefore, the resection and sorting of N1 station LNs in lung cancer is crucial. Besides mediastinal and hilar LN metastasis, PLN metastasis should be taken into consideration when segmentectomy is conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al . conducted a prospective study and the results showed that it was possible for lung cancer to metastasize to the unaffected segment within the same lobe . Therefore, the resection and sorting of N1 station LNs in lung cancer is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the probability of finding iLNs in cN0 patients was high. Of 196 patients operated on by lobectomy for stage I NSCLC, there were 36 pN1s and of these 36 pN1s, 28 were iLNs and 30 were aLNs ( 30 ). It is thus important to find indicators of the potential presence of these LN.…”
Section: The Influence Of the Location Of The Segmental Nodesmentioning
confidence: 99%
“…At present, we only have an indirect indicator, i.e., the examination of adjacent nodes. In the above-mentioned study of Xiao et al the probability of being iLNs positive was 40% when an aLN was invaded ( 30 ). The authors concluded that when an aLN was metastatic at frozen section, segmentectomy should not be recommended and resection should be extended to lobectomy.…”
Section: The Influence Of the Location Of The Segmental Nodesmentioning
confidence: 99%